Behavioural Intention of Dentists in Using Industrial Revolution 5.0 Technology In Dental Services: A Qualitative Study in Klang Valley, Malaysia - Ali, Siti Zaffira Sheik; Nasir, Nurul Farhana Mohd; Rosli, Nurul Athira; Hashim, Muhammad Faqih; Sharkawi, Sharizan (Advances in Social Sciences Research Journal, 2024)
The adoption of Industrial Revolution 5.0 (IR 5.0) technology has been a significant development in the dental industry, promising to improve patient outcomes, streamline workflows, and enhance the overall quality of dental services. However, the uptake of this technology among dentists has been slow. This paper aims to explore the behaviour intention of dentists in using IR 5.0 technology in their dental services, by examining the factors that influence their decision making. Semi-structured interviews were conducted with 5 dentists working in the private dental clinics in Klang Valley, Malaysia. The findings suggest that the dentists' intention to adopt the technology is driven by internal factors such as performance expectancy, financial, effort expectancy, sentiments; and external factors such as facilitating conditions and social influence. The results highlight the need to address the barriers and concerns associated with adopting new technologies in the dental industry.